Quais saberes são mobilizados para suprir as lacunas na formação inicial referentes à história da ciência? - Takahashi, Bruno Tadashi; Bastos, Fernando (Góndola, enseñanza y aprendizaje de las ciencias, 2014)
Nowadays it is increasingly required insertion History of Science on content to be worked in education, which raises many doubts and difficulties on the teachers did not have that content in their initial training. This work results from a qualitative empirical study aimed to investigate how a teacher of Biology and Science in a public school in the city of Bauru, São Paulo state, was not in their initial training courses relating to the History of Science, mobilizes their knowledge to enter such an approach in their teaching practice. In the research methodology used as its theme the history of DNA present in the materials and also conduct open interviews and field notes to identify the knowledge involved in teaching practice and was adopted as the theoretical framework of Maurice Tardif’s Teachers Knowledge. The results showed that even with difficulties arising from gaps in initial training teachers used their experiential knowledge to fill these needs, as well as appropriating knowledge from the programs and textbooks, but their shortcomings make it difficult to analyze more critically. Thus, these data lead us to a reflection on the role of textbooks for these teachers and the process by which the knowledge they construct occurs.